THE EFFECT OF WHEAT TYPE AND METHOD OF EXPOSURE IN RESPONSE KHABRA BEETLE TO MICROWAVE RADIATION - Emad Al-Ebady (Mesopotamia Journal of Agriculture)
The results of the recent study of the effect of the wheat variety (Hard Tamuz 2 and Soft Semito) and method of insect exposure to microwave radiation (mixed and un mixed with food) to energy level 200, 500, 800 watt to different exposure times zero, 15, 30, 45, 60, 90 Sec. revealed the killing percentage in adults, larvae, pupae were varied according to the wheat variety and reached for hard and soft variety 40%, 32.59% for adults, 32.87%, 30.15% for larvae and 38.15%, 41.39% for the pupae. The results also showed that the killing percentages were higher when exposed the insects and food together in comparison with the exposed insect only, and reached 40.19%, 32.41% for adults and 32.59%, 30.46% for larvae and 41.39%, 38.15% for the pupae. The killing percentage mean of the insects stages proportionally increased with increasing the energy level 200, 500, 800 watt and reached 17.36%, 42.64% and 48.89% for adults and 6.94%, 34.86% and 52.78% for larvae and 24.86%, 35.14% and 59.31% for the pupae. The results also exhibited that the killing percentage of insect stages were increased with increasing the exposure time.